2023
DOI: 10.3390/ijms241512361
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Response Kinetics after 60 Minutes at Different (1.4 ATA and 2.5 ATA) Hyperbaric Hyperoxia Exposures

Abstract: Hyperbaric oxygen therapy (HBOT) is a therapeutical approach based on exposure to pure oxygen in an augmented atmospheric pressure. Although it has been used for years, the exact kinetics of the reactive oxygen species (ROS) between different pressures of hyperbaric oxygen exposure are still not clearly evidenced. In this study, the metabolic responses of hyperbaric hyperoxia exposures for 1 h at 1.4 and 2.5 ATA were investigated. Fourteen healthy non-smoking subjects (2 females and 12 males, age: 37.3 ± 12.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“… Leveque et al (2023) , reported comparable levels of ROS, upon 30 min of HBOT under 1.4 ATA and 2.5 ATA of 100% oxygen which peaks after 2 h of treatment. However, another study has shown no significant changes in the plasma ROS levels after 75 min of HBOT at 2.5 ATA of 100% oxygen ( de Wolde et al, 2022 ; Leveque et al, 2023 ). Thus, the course of treatment in using HBOT depends mostly on the symptomatic factors and initial response to the treatment.…”
Section: Effect Of Hbot On Aging and Cellular Regenerationmentioning
confidence: 86%
See 2 more Smart Citations
“… Leveque et al (2023) , reported comparable levels of ROS, upon 30 min of HBOT under 1.4 ATA and 2.5 ATA of 100% oxygen which peaks after 2 h of treatment. However, another study has shown no significant changes in the plasma ROS levels after 75 min of HBOT at 2.5 ATA of 100% oxygen ( de Wolde et al, 2022 ; Leveque et al, 2023 ). Thus, the course of treatment in using HBOT depends mostly on the symptomatic factors and initial response to the treatment.…”
Section: Effect Of Hbot On Aging and Cellular Regenerationmentioning
confidence: 86%
“…The overall result of repeated HBOT exposures is the generation of a protective cellular environment with minimal oxidative damage. The treatment conditions for utilizing HBOT to generate anti-oxidant effects has been found to be varied in different studies ( Balestra et al, 2022 ; de Wolde et al, 2022 ; Leveque et al, 2023 ; MacLaughlin et al, 2023 ). Leveque et al (2023) , reported comparable levels of ROS, upon 30 min of HBOT under 1.4 ATA and 2.5 ATA of 100% oxygen which peaks after 2 h of treatment.…”
Section: Effect Of Hbot On Aging and Cellular Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is interesting to note that despite a constant daily variation, we observe a progressive build-up of ROS and 8-iso-PGF2 while this is not the case for DNA damage. This suggests that the complex endogenous antioxidant system, including enzymes such as superoxide dismutase, GSH and catalase is exceeded ( Leveque et al, 2023 ). Therefore, we can assume that these different mechanisms may combine themselves and when oxy-inflammation reaches a certain level, it exceeds hormetic coping mechanisms, which is also suggested by the strong correlation between the duration of exposure in days and inflammatory markers (ROS, lipid peroxidation, Neopterin and IL-6).…”
Section: Discussionmentioning
confidence: 99%
“…This transient toxic substance of minute quantity is now known to be reactive oxygen species ( 2 , 55 ). ROS/oxidative stress have been shown to occur with single HBOT exposures at both 1.5 and 2.4 ATA ( 56 ). ROS and their by-products in OT seizures in animals have demonstrated permanent effects, including lipid peroxidation ( 3 ), apoptosis ( 57 ), cognitive injury ( 58 ), motor deficits ( 46 ), and ischemic lesions ( 11 ).…”
Section: Discussionmentioning
confidence: 99%